Dynamic Representation of Barriers for Adopting Building Information Modelling in Malaysian Tertiary Education (Construction Economics and Building, 2018)
Building Information Modelling (BIM) is deemed to shape the future of the construction sector across the world. At present, the lack of BIM in tertiary education has been the rising concern around the world as the demand for BIM talent increases. The current landscape suggests that few pedagogic researches have been undertaken to advance BIM education, particularly in Malaysia. BIM implementation could only be possible by identifying the potential barriers, which is a basic pre-requisite for successful adoption of BIM. Unfortunately, previous studies on the barriers of BIM adoption have often based on theoretical constructs, which are deterministic in nature. The methodology used could not portray a conclusive correlation of causal relations among the variables, creating difficulty in developing holistic and workable solutions. Therefore, this study aims to develop a methodology that provides a dynamic representation of the barriers in implementing BIM in tertiary education. The methodology combines both the deterministic (feedback from questionnaire survey) and dynamic approach (causal loop diagram). Data was first collected and analysed through a questionnaire survey administered among lecturers from selected Malaysian universities. Following that, a dynamic systems approach (causal loop diagram) was used to demonstrate the complex nature and interrelationship of the barriers for a more holistic representation. Results from the deterministic analysis has suggested barriers that relate to technology, while findings from the dynamics has identified the people aspect as the core barrier for BIM adoption. This study has contributed in establishing a methodology that integrates the dynamic approach with the deterministic data towards providing a more holistic representation of a system that further enables the identification of holistic solutions that would address the core barriers inhibiting the implementation of BIM education, particularly at Malaysian Universities.